STRATEGIC ROLE OF HUMAN CAPITAL IN NAVIGATING HYBRID MARKETINGCUSTOMER-BASED IN CREATIVE INDUSTRIES IN THE AI ERA: AN SLR STUDY - Junef Ismailiyanto; Iman Hasan Ansyari MN (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Digital transformation triggered by advances in artificial intelligence (AI) has driven the emergence of various new marketing models, including hybrid marketing (HM) that combines digital and traditional approaches; offline and online. Amidst these changes, the strategic role of Human Capital (HC) becomes crucial, especially in the creative industry that relies heavily on innovation, empathy, and customer engagement. This study aims to systematically explore how academic literature defines, conceptualizes, and evaluates the contribution of HC in the implementation of customer-based HM in the AI ​​era, focusing on the creative industry sector. The Systematic Literature Review (SLR) method was used based on the PRISMA 2020 protocol. The literature was taken from the Scopus, SpringerLink, and Emerald Insight databases with a scope of publications from 2015 to June 10, 2025. Of the 8,297 articles identified, 65 articles were reviewed systematically and thematically. The findings group four main themes: (1) the strategic role of HC in guiding customer-based HM in the AI ​​era; (2) adaptive competency of HR towards technology integration; (3) human-AI synergy in customer value creation; (4) the role of empathy, creativity, and soft skills in maintaining emotional closeness to customers; and (5) the challenges of digital transformation to marketing structures and functions in the creative industry. Practical implications include the need for HR reskilling, organizational transformation, and strengthening customer-based marketing strategies. The novelty of this study lies in the synthesis of literature that connects HC, AI, and hybrid marketing in the creative industry landscape. Its theoretical contribution opens up space for further exploration of customer-oriented human–AI collaborative models.